Digital Forensic Methods: Unraveling Scholarly Trends in Legal Contexts - Mayasari, Sephia; Phahlevy, Rifqi Ridlo; Fiddina, Irta (Proceedings of The ICECRS, 2023)
This study scrutinizes 264 scholarly articles from 2012 to 2022, exploring the intersection of digital forensics and legal methodologies. Noteworthy findings reveal prolific contributions from institutions like the University of Lausanne and University College Dublin, showcasing 2019 as a peak year with 42 publications. Computer Science dominates, encompassing 223 articles, with Graeme Horsman emerging as a prominent author with 13 publications. The UK leads in scholarly activity, generating 74 articles, while Elsevier stands out as the primary publisher with 145 articles. This research serves as a vital resource, offering guidance for further exploration in the dynamic realm of digital forensics and legal methods. Highlights : Analysis of 264 articles at the intersection of digital forensics and legal methodologies Reveals notable contributions from specific institutions and leading authors Offers guidance for further exploration in this dynamic field Keywords: Digital Forensic, Methods, Scholarly Landscape, Interdisciplinary Research, Legal Methodologies